Alcohol Abuse as a Cause of Poor Academic Performance among Social Science Students of the University of Calabar, Nigeria - Ukwayi, Joseph K.; Lucy , Ambekeh U.; Chibuzo, C. Uwanede; Undelikwo, Veronica. A. (Mediterranean Journal of Social Sciences, 2013)
Alcohol abuse cut-short the academic vision of colleges and universities and may undermine their aspiration of molding futurecitizens. In Nigeria, alcohol consumption has found its way among undergraduate students, who are normally seen in bars andrestaurants including other secluded areas some metres away from the school consuming alcohol. The study examined theeffects of alcohol abuse on the academic performance of Social Science Students of the University of Calabar, Nigeria. Datawas obtained through the administration of 120 copies of questionnaires to students of the faculty of Social Sciences ofUniversity of Calabar, Nigeria. The Participants were approached at their lecture rooms and popular hang-outs within thefaculty. Their ages ranged from 15 to 35 years and above. The result revealed that majority of the participants were within theage group of 15 – 35 years, which indeed is the age of risky behaviour characterized by substances use and abuse. For fun,stay wake (not to sleep during lectures and to read at night) and for courage (to be able to approach lecturers and make apublic address) were identified as the primary reasons for the consumption of alcoholic beverages. The study further indicatedthat alcohol abuse had significant influence on students’ academic performance (F = 70.115, p<0.01), and that a unit increasein alcohol abuse would result in 61% of social science students performing poorly in their examinations. The studyrecommends daily counseling as a way to reduce this phenomenon and improve students’ performance in tertiary institutions,as well as advising students to take alcohol lightly while in school.